Kinematics and joints moments profile during straight arm press to handstand in male gymnasts - Mizutori, H.; Kashiwagi, Y.; Hakamada, N.; Tachibana, Y.; Funato, K. (PLOS ONE, 2021)
Biomechanical features of the handstand, one of the most fundamental skills required for artistic gymnastics events, have not been well documented. The purpose of this study was to clarify the kinematics and joint moment profiles during straight arm press to handstand in different highly skilled male gymnasts. Fifty-nine male gymnasts performed a straight arm press to handstand on a force platform and were judged on their performance by experienced certified judges. Subjects were divided into two groups (highly-skilled and less-skilled). Kinematic data were obtained using a video camera synchronized with force platform. Joint moments (wrist, shoulder, hip) during each straight arm press to handstand were calculated using the inverse dynamics solution. Larger shoulder flexion moments were observed in less-skilled compared with highly- skilled performers (at 3-59%, p < 0.001) while larger hip flexion moments were observed in highly- skilled performers at 52% (p = 0.045) and 56% (p = 0.048) and normalized time of straight arm press to handstand. Major differences between highly-skilled and less-skilled performers were observed in hip joint moment production as it shifted from extension to flexion from the leg horizontal position to the handstand position in highly-skilled gymnasts. Successful straight arm press to handstand techniques observed in highly-skilled performers were characterized as a more acute pike position at toe-off as well as hip flexor moments at latter phase of the straight arm press to handstand.